2012
DOI: 10.3346/jkms.2012.27.11.1327
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Disease Severity Are Correlated in Patients with Atopic Dermatitis

Abstract: Quantification of quality of life (QOL) related to disease severity is important in patients with atopic dermatitis (AD), because the assessment provides additional information to the traditional objective clinical scoring systems. To document the impact of AD on QOL for both children and adults as well as to quantify the relationship with disease severity, QOL assessments were performed over a 6-month period on 415 patients with AD. A questionnaire derived from the Infants' Dermatitis Quality of Life Index (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 23 publications
12
72
2
3
Order By: Relevance
“…Thus, it was confirmed that as the disease duration increased, the life quality decreased [8,28,29], accompanied by more and more intensive feelings of helplessness and dissatisfaction with one's health and intensified care for external appearance. AD patients battle against the disease for many years and even the whole life, making immense day-to-day efforts to get rid of symptoms of the disease and mitigate the suffering.…”
Section: Omówieniementioning
confidence: 57%
See 1 more Smart Citation
“…Thus, it was confirmed that as the disease duration increased, the life quality decreased [8,28,29], accompanied by more and more intensive feelings of helplessness and dissatisfaction with one's health and intensified care for external appearance. AD patients battle against the disease for many years and even the whole life, making immense day-to-day efforts to get rid of symptoms of the disease and mitigate the suffering.…”
Section: Omówieniementioning
confidence: 57%
“…Tym samym potwierdzono, że wraz z czasem trwania choroby obniża się jakość życia [8,28,29], wzrasta poczucie bezradności i niezadowolenie ze stanu zdrowia oraz zwiększa się dbałość o wygląd zewnętrzny. Pacjenci z AZS przez wiele lat, a czasem przez całe życie podejmują ogromny, codzienny wysiłek, aby pozbyć się objawów chorobowych i zminimalizować swe cierpienie.…”
Section: Resultsunclassified
“…Although previous studies investigated the impact of AD on children and their family [8910], little is known in dynamics among various factors associated with QoL in children and their family, particularly severity of disease and psychosocial aspects of parents such as life satisfaction and parenting stress. Therefore, this study aimed to examine the family QoL and associated factors of children with AD and parents, particularly focused on disease severity and psychosocial factors of parents.…”
Section: Introductionmentioning
confidence: 99%
“…DLQI and ISS are reported in some of the pruetic conditions, listed in Table 4, with a review of the literature (6)(7)(8)(9)(10)(11)(12)(13). Our findings show that reactions to tattoos and their affection on quality of life attains the level of the above mentioned skin diseases, diseases that normally affect a much larger area than the typical tattoo reactions do.…”
Section: Discussion/conclusionmentioning
confidence: 47%